A Mini Review on Analysis of Potential Antibacterial Activity of Symbiotic Bacteria from Indonesian Freshwater Sponge: An Unexplored and A Hidden Potency - Setiawan, Edwin; Hermanto, Michael Einstein; Abdulgani, Nurlita; Prasetyo, Endry Nugroho; Riani, Catur; Wulandari, Dyah; Budiharjo, Anto (Journal of Tropical Biodiversity and Biotechnology, 2024)
Marine sponges have been investigated as potential bioresources because of their symbiotic relationship with microbes such as Actinobacteria that produce antibacterial substances. In contrast, a group of sponges, that inhabits freshwater environments called freshwater sponges (Order Spongillida Manconi & Pronzato, 2002) and consists of only one percent among all of the sponges’ species (Phylum Porifera Grant, 1836), has  not yet intensively examined.  For this reason, we screened, determined, evaluated, and reviewed by examining several databases in Scopus, Pub Med, and Google Scholar related to potential aspects of symbiotic bacteria and their antibacterial substances that can be further utilised  and developed into synthesised  antibacterial compounds, based on published metagenomic data of symbiotic bacteria in freshwater sponges. At the same time, we compared a composition of those freshwater symbionts to marine sponges’ symbionts whether those possess a similar composition or not. Moreover, a current report and a revisit study of freshwater sponges in East Java, initiate further direction on mapping of those symbiotic bacteria from Indonesia that can be nominated as potential groups possessing antibacterial properties.